The haunting of Hajji Hotak : and other stories - Kochai, Jamil Jan, 1992- (Viking, 2022)
"A luminous meditation on sons and fathers, ghosts of war, and living history that moves between modern-day Afghanistan and the Afghan diaspora. In playing "Metal Gear Solid V," a young man's video game experience turns into a surreal exploration on his own father's memories of war and occupation. A college student in "Hungry Ricky Daddy" starves himself in protest of Israeli violence against Palestine. Set in Kabul, "Return to Sender" follows a doctor couple who must deal with the harsh realities of their decision to stay as the violence grows and their son disappears. And in the title story, "The Haunting of Hajji Hotak," we learn the story of a man codenamed Hajji, from the perspective of a government surveillance worker, who becomes entrenched in the immigrant family's life"--